Measles Infection and Vaccination Status against Measles in Children during 2019-2020: A Hospital Based Study in Chattogram - Ferdousi, Asma; Datta, Mitra; Mamtaz, Sayeda Shahnoor Hasina; Jahan, Rifat; Hoque, Salina; Samad, Rasheda (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2023)
Background: Despite widespread availability of a safe and cost-effective vaccine, Measles outbreak is reported from different regions of Bangladesh in the recent past. This study was aimed to Identify the related features of Measles infection in children during the upsurge of Measles infection in Chattogram during 2019-2020, when Bangladesh was about to achieve Measles elimination. Materials and methods: This prospective observational study included all the Measles infected children admitted in the Pediatric Ward of Chittagong Medical College Hospital, Chattogram during the period from September 2019-February 2020. In this hospital patients up to 12 years after neonatal period are admitted. Patients whose guardian did not give consent were excluded. Measles cases were diagnosed clinically according to case definition criteria by WHO. Demographic, clinical features, Measles vaccination status of both affected children & their mother and associated complications were recorded in a predesigned form. Data were analyzed and results were given in a tabulated form. The aim of this study was to evaluate the characteristics of Measles infection and their vaccination status in children during its upsurge in 2019-2020. Results: Affected children 13(20%) were suffered in spite of vaccination. Among the 65 affected children 44 (67.6%) were below one year of age, youngest one was 2 months old. Male to female ratio was 1.8:1. 80% (n=52) children were not vaccinated, 35 of them not yet attained the age of vaccination. 17 children attained the age but vaccination was delayed due to cough and cold, fever, bronchopneumonia or Measles itself. Complications were common among them, Bronchopneumonia 47 (72.3%) and Purulent conjunctivitis 38 (58.5%). There was no case fatality. Conclusion: Children are being affected by Measles before attaining the age of first dose of vaccination and incompletely vaccinated or unvaccinated children have a role in the upsurge of Measles. Chatt Maa Shi Hosp Med Coll J; Vol.22 (1); January 2023; Page 33-37